Molecular Pathogenesis of Avian Splenic Injury Under Thermal Challenge: Integrated Mitigation Strategies for Poultry Heat Stress - Qing Liu; Lizhen Ma; Lili Liu; Ding Guan; Zhen Zhu; Xiangjun Hu (Current Issues in Molecular Biology)
Heat stress (HS), an important environmental stressor for healthy poultry farming, has been shown to have a detrimental effect on production performance and induce serious diseases through immune system damage. As the avian peripheral immune system’s primary organ, spleen is subject to complex biological processes in response to HS injury. Histopathological characterization demonstrated that HS resulted in the destruction of the splenic red and white medulla, a decrease in cell density and organ atrophy. These changes directly impaired pathogen clearance and immune surveillance. At the physiological level, the impact of HS is characterized by disrupted metabolic homeostasis through interrupting neuroendocrine function. This, in turn, results in a significant suppression of humoral immune response. The oxidative-inflammatory cascade constitutes the core pathology of this disease. Energy metabolism disorder triggered by mitochondrial dysfunction and redox imbalance form a vicious circle, which promotes apoptosis signaling cascade. Meanwhile, over-activation of intrinsic immune system triggers a series of inflammatory factors, which further amplifies effects of tissue damage. The present prevention and control strategies are centered on synergistic anti-inflammatory and antioxidant interventions with nutrient modulators and plant actives. Nevertheless, it is imperative for future studies to incorporate multi-omics technologies in order to analyze the metabolic mechanisms and patterns of stress and establish a precise intervention strategy based on immune homeostatic regulation. This review systematically investigated the multilevel regulatory mechanisms of HS-induced spleen injury, which provides a theoretical basis for the mechanistic analysis and technological innovation of the prevention and control of HS syndrome in poultry.